Prevalence of Extended-Spectrum Beta Lactamase-Producing Microorganisms in Dr. Mohammad Hoesin Hospital Palembang - Phey Liana; Norlaila Binti Chahril; Sri Nita; Tungki Pratama Umar (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Production of Extended-Spectrum Beta-Lactamase (ESBL) by Enterobacteriaceae continues to be a problem of infectious diseases, especially in hospitals. The main causes of ESBL-producing bacteria colonization are urinary tract infections, length of hospital stay, invasive medical equipment, and antibiotics usage. This study aims to compare the incidence of ESBL based on the type of organism in Dr. Mohammad Hoesin Hospital for the 2017 and 2018 periods. The research design used was descriptive with a cross-sectional approach, which used secondary data at the Clinical Pathology Department of Dr. RSUP. Mohammad Hoesin Palembang. The findings of this study showed a decreasing pattern in the incidence of ESBL in 2017 and 2018, but with a similar pattern which was dominated by Klebsiella pneumoniae (followed by Escherichia coli and Klebsiella ozaenae), inpatients in pediatric wards, internal medicine, and intensive care units, and on sputum specimens. This study showed the presence of high levels of ESBL-producing bacteria (>60%) in Dr. Mohammad Hoesin Hospital, which was mainly caused by Klebsiella pneumoniae.